Exploring the shape and distribution of electrodes in membraneless enzymatic biofuel cells for high power output. (13th May 2021) - Huang, Xingcan; Zhang, Jiru; Su, Hang; Sun, Fengyun; Lu, Zipeng; Su, Ang; Liu, Jian
Abstract: Enzymatic biofuel cells (EBFCs) have great application prospects by catalyzing the redox reaction of biofuels to generate electricity. In order to further improve the output performance of EBFCs, the influences of electrode shape and array on the outputs of EBFCs were investigated by finite element analysis. The relationship between electrode shapes and the distribution of field strength and voltage were firstly explored by graphical method. According to simulation results, circular electrodes distribution would be the best choice for EBFCs with a maximum power density (MPD) of over 4.7 mW cm −2 and the least current density range of 4.4 mA cm −2 under ideal conditions. The hexagonal close-packed array was able to distribute more electrodes and thus obtain higher total power outputs. For the monopolar plate EBFCs, anodes and cathodes were interlaced on the same plate to facilitate the application of wearable and implantable devices. Moreover, the network topology theory was applied to the design of electrode array in EBFCs, which provided extensive electrode array structures for EBFCs. The results exhibited that the MPD of radial and star topologies were both about 4.7 mW cm −2, while that of ring topology was much smaller. The electrode shape and electrode array studied in this paper would be of great significance to the structural design of EBFCs devices. Highlights: Reasonable electrodes shapes and arrays were studied for improving the output of EBFCs. Two device structures of membraneless EBFCs were proposed for the applications. Finite element analysis was used to compare the output of different EBFCs models.